Accuracy of qualitative and quantitative cranial ultrasonographic markers in first‐trimester screening for open spina bifida and other posterior brain defects: a systematic review and meta‐analysis. (25th October 2020) - Mace, P; Mancini, J; Gorincour, G; Quarello, E
Abstract : Background: The significant number of qualitative and quantitative ultrasound markers described for first‐trimester screening of open spina bifida (OSB) and other posterior brain defects (oPBD) has resulted in their complex implementation and interpretation for a widespread screening and in a lack of consensus regarding diagnostic accuracy. Objectives: To assess and compare the accuracy of qualitative and quantitative cranial sonographic markers at 11–14 weeks of gestation for the detection of OSB and oPBD. Search strategy: A systematic literature search was performed in MEDLINE and COCHRANE from 2009 to April 2020. Selection criteria: Studies assessing the diagnostic accuracy of quantitative and/or qualitative ultrasound signs to predict OSB and oPBD were included. Cohort studies and case–control studies were also considered. Data collection and analysis: Two reviewers independently extracted data and assessed the risk of bias. The overall pooled estimate and a summary receiver operating characteristic curve was estimated for each subgroup (qualitative and quantitative assessment). Main results: Twenty‐three studies were included in our meta‐analysis. The pooled sensitivity and specificity for qualitative assessment were 76.5% and 99.6%, and for quantitative assessment were 84.5% and 96.3%, respectively; specificity for the qualitative ultrasound signs was significantly higher ( P  = 0.001). The overall sensitivity of cranial sonographic markers for the screening of oPBD was 76.7% and specificity was 97.5%. Conclusions: The qualitative approach demonstrated greater specificity, so this would appear to be more appropriate for daily screening, as a first‐line tool, whereas the quantitative approach should be reserved for expert ultrasound. Tweetable abstract: This study highlights the relevance of first‐trimester qualitative ultrasound signs in the screening of open spina bifida. Tweetable abstract: This study highlights the relevance of first‐trimester qualitative ultrasound signs in the screening of open spina bifida.